Does an Ileoanal Anastomosis Decrease the Rate of Successful Pregnancy Compared With an Ileorectal Anastomosis? A National Study of 1491 Patients. Issue 5 (15th May 2023) - Challine, Alexandre; Voron, Thibault; O'Connell, Lauren; Chafai, Najim; Debove, Clotilde; Collard, Maxime K.; Parc, Yann; Lefèvre, Jérémie H.
Abstract : Objective: Report the rate of successful pregnancy in a national cohort of women with either an ileal pouch anal (IPAA) or ileorectal (IRA) anastomosis constructed after colectomy for inflammatory bowel disease (IBD) or polyposis. Background: Fertility after IPAA is probably impaired. All available data are corroborated by only small sample size studies. It is not known whether construction of IPAA versus IRA influences the odds of subsequently achieving a successful pregnancy, especially with increased utilization of the laparoscopic approach. Methods: All women (age: 12–45 y) undergoing IRA or IPAA in France for polyposis or IBD, between 2010–2020, were included. A control population was defined as women aged from 12 to 45 years undergoing laparoscopic appendicectomy during the same period. The odds of successful pregnancy were studied using an adjusted survival analysis. Results: A total of 1491 women (IPAA=872, 58%; IRA=619, 42%) were included. A total of 220 deliveries (15%) occurred during the follow-up period of 71 months (39–100). After adjustment, the odds of successful pregnancy was not significantly associated with type of anastomosis (after IPAA: Hazard Ratio [HR]=0.79, 95% confidence interval=0.56–1.11, P =0.17). The laparoscopic approach increased the odds of achieving successful pregnancy (HR=1.79, 95% confidence interval=1.20–2.63, P =0.004). IRA and IPAA significantly impacted fertility when compared with the control population ( P <0.001). Conclusions: In this large cohort study, total colectomy for polyposis or IBD was associated with reduced fertility compared with the general population. No difference in odds of achieving successful pregnancy was found between IRA and IPAA after adjustment. This analysis suggests laparoscopic surgery may be associated with greater likelihood of pregnancy.